Dai Ghiacci allo Spazio - Enrico Mazzoli; Laura De Santis; MESSEROTTI, MAURO; SALVI, Gianguido (Biblion Edizioni, 2008)
The First International Polar Year was born from an idea of the Austro-Hungarian Naval lieutenant, Carl Weyprecht. Coming back to Trieste, Italy, from his expedition in the Arctics, Weyprecht developed his plan for setting up a new collaborative, circumpolar research, which would significantly replace the way to organize polar expeditions. In his essay “Fundamental Principles of Arctic Research” Weyprecht promoted the systematic exploration of polar regions through international cooperation and the scientific dissemination of results. Such a concept was presented in September 1875 at the 4th Meeting of the Association of German Naturalists and Physicists at Graz. In 1879 the International Meteorological Congress met in Rome and recognized the importance of Weyprecht’s proposal. On the occasion of the 4th International Polar Year 2007-2009, this book reconstructs the preliminary facts and the genesis of the IPY, through an historical analysis of the cultural and political reasons that allowed the rising of a new scientific approach. The first part of the book documents with original details the social and cultural life as it was in Trieste, one of the most important Austro-hungarian harbours, at the end of the 19th century, in which Carl Weyprecht operated. The second part of the book illustrates the development of the Italian Antarctic Program, after the Antarctic Treaty and the involvement of the Italian scientific community into the International Polar Year. In the last section the main scientific steps achieved in the 19th and 20th centuries and the development of parallel initiatives to IPY, such as, the International Year of Planet Earth, the International Heliophysical Year, the International Geophysical Electronic Year, are briefly illustrated.